If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -38 = 46x + 6 Reorder the terms: -38 + 5x = 46x + 6 Reorder the terms: -38 + 5x = 6 + 46x Solving -38 + 5x = 6 + 46x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-46x' to each side of the equation. -38 + 5x + -46x = 6 + 46x + -46x Combine like terms: 5x + -46x = -41x -38 + -41x = 6 + 46x + -46x Combine like terms: 46x + -46x = 0 -38 + -41x = 6 + 0 -38 + -41x = 6 Add '38' to each side of the equation. -38 + 38 + -41x = 6 + 38 Combine like terms: -38 + 38 = 0 0 + -41x = 6 + 38 -41x = 6 + 38 Combine like terms: 6 + 38 = 44 -41x = 44 Divide each side by '-41'. x = -1.073170732 Simplifying x = -1.073170732
| -6+3y=-18 | | 15x-11x+3x=7 | | Z-7/9=z/9 | | 6c+c-5c+2c-2c=20 | | x^2-2(2.8)x-6=0 | | -3x+5x+2=28 | | -.75b=2 | | 16w^2=1 | | 8z-6z-2z+z+2z=12 | | 5/2p+1/6 | | -6(3.5)+3y=-18 | | 9x+39+5x=41 | | n-.75=2.75 | | 3x+5x+4=36 | | 4r+5r-6r-r=10 | | a^1/2/a^2 | | 88=2L+2(19) | | 6x-7(-2x-4)=-112 | | 5+1.1x=29 | | 19n-18n=17 | | -6x+3=-18 | | (2c+s)+4h+4(h+f+m)-3(h+s)= | | 20=-6x+2 | | -4-2a+11=6a-13 | | 16w-13w=18 | | -4=r/4-5 | | -3=-4x-15 | | (v-1)(v+7)= | | 23-(-6z-9)+11z=7-9z | | 2r^2-7r-16=0 | | -7(-8k+1)=-343 | | 3x+3(-6x+12)=186 |